Pengaruh Kepemilikan Pemerintah Terhadap Pengungkapan Materialitas pada Laporan Keberlanjutan (Studi Empiris pada Perusahaan Milik Pemerintah yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Ryasta, Kadek Dwianggra; Wirama, Dewa Gede (Universitas Pahlawan Tuanku Tambusai, 2024)
This study is purpose to obtain empirical evidence of government ownership effect to the materiality disclosure. Four control variables were operated in this research, namely profitability, leverage, independent commissioner, and industry type. This research was conducted on all government-owned companies listed on Indonesia Stock Exchange for the 2018-2022 period. The sampling method uses the non-probability sampling method with purposive sampling techniques. There are 19 companies that met the sample criteria, with a total of 95 observations. The results of the analysis find that government ownership has a positive effect on materiality disclosure.